Ownership concentration and performance of deteriorating syndicated loans - Mariassunta Giannetti; Ralf R. Meisenzahl (Federal Reserve Bank of Chicago, 2021)
Regulation and capital constraints may force banks and collateralized loan obligations (CLOs) to sell deteriorating loans, potentially hampering renegotiation and amplifying the initial negative shock to the borrower. We show that banks and CLOs sell downgraded loans to mutual funds and hedge funds. The reallocation of loan shares favors the syndicate's concentration, increasing lenders' incentives to renegotiate. However, syndicates remain less concentrated when potential buyers experience financial constraints and subsequently loans are less likely to be amended and more likely to be downgraded even further. Our findings indicate that existing regulations may amplify shocks to credit quality during periods of generalized distress in the financial system.
Keywords: G21; 330; Debtor Concentration; Credit Quality; Leveraged Lending